1984
DOI: 10.1093/oxfordjournals.eurheartj.a061730
|View full text |Cite
|
Sign up to set email alerts
|

Exercise capacity with transdermal nitroglycerin in patients with stable angina pectoris

Abstract: Transdermally delivered nitroglycerin (TTS-NTG) through a rate-controlling membrane yields stable blood levels for 24 h. We studied the effect of TTS-NTG (25 mg per 10 cm2) on exercise induced angina in 10 patients with stable angina pectoris, all in NYHA class III, who were not under treatment with other cardiac drugs. In a pre-study exercise test, all patients had angina pectoris and more than one mm ST depression. The study was placebo controlled and double blind with a randomized cross-over. Exercise tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Eleven previous studies relating to efficacy in angina pectoris have been published, of which eight have demonstrated variable clinical benefit whilst three have shown no measurable effect whatever. [8][9][10][11][12][13][14][15][16][17][18] The discrepancy between the studies is principally related to the dose regime and the presence or absence of concomitant anti-anginal medication. The three studies showing no demonstrable effect utilized a fixed dose protocol of one nitrate patch delivering 5 mg per 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Eleven previous studies relating to efficacy in angina pectoris have been published, of which eight have demonstrated variable clinical benefit whilst three have shown no measurable effect whatever. [8][9][10][11][12][13][14][15][16][17][18] The discrepancy between the studies is principally related to the dose regime and the presence or absence of concomitant anti-anginal medication. The three studies showing no demonstrable effect utilized a fixed dose protocol of one nitrate patch delivering 5 mg per 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, comparison of the two placebo treatment periods (pretreatment and washout, see Table 3) confirmed that the frequency of angina attacks reduced and exercise tolerance improved with time. In any cross-over study, it is important that patients enter both active treatment periods in the same clinical state, but the effect of these changes was minimized by comparing the differences from base- (Cerri et al, 1984;Hollenberg & Go, 1984;Naafs et al, 1984;James et al, 1985) and repeated administration (Georgopoulos et al, 1982;Letzel et al, 1982;Hollenberg & Go, 1984). In contrast, other studies have failed to demonstrate a therapeutic effect (Crean et al, 1984;Parker & Fung, 1984;Dickstein & Knutsen, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…New formu-lations of transdermal nitrate (TN) have been described, which control the release of nitroglycerin from a drug reservoir (Shaw & Urquhart, 1981;Muller et al, 1982). Initial studies have suggested that TN is effective at reducing the frequency of anginal attacks (Garnier et al, 1982;Letzel & Johnson, 1984), and some controlled trials have supported this observation (Georgopoulos et al, 1982;Letzel et al, 1982;Thompson, 1983;Cerri et al, 1984;Hollenberg & Go, 1984;Naafs et al, 1984). More recently, several studies have failed to demonstrate a *Present address and correspondence: Royal Victoria Hospital, Belfast BT12 6BA, Northern Ireland therapeutic effect of TN (Crean et al, 1984;Parker & Fung, 1984;Reichek et al, 1984;Dickstein & Knutsen, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…These systems continuously release nitroglycerin by matrix diffusion-controlled or membrane permeationcontrolled drug delivery systems and result in an elevated nitroglycerin blood level that persists for at least 24 hours (19,20). The results of reported placebo-controlled studies are contradictory; some show a complete failure of transdermal nitroglycerin to enhance exercise capacity in patients with angina pectoris (21,22), whereas other studies show a beneficial effect (23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). In addition, the results of studies about the persistence of the antianginal effect of transdermal nitroglycerin have conflicted.…”
Section: Evidence For Nitrate Tolerancementioning
confidence: 99%